EFEKTIVITAS TERAPI BERMAIN DENGAN MEWARNAI PADA ANAK CACAT DI YPAC KOTA MAKASSAR - Pawenrusi, Esse Puji; Zulkarnaen, Iskandar (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2018)
This therapy aims to improve the effectiveness of play in children so that children will not lose theright to play. According to the data in SLB YAPC Makassar city children who were educated therein 2016/2017 is 130 children. So that there are 130 children who are likely to lose effectiveness inplay, if this is allowed then the right child in play will just passed. Because even if the child is sick,but the need for play still exists. Data collection using obeservation and interviews. The dataobtained were analyzed using pre and post test without control in the conditions presented in theform of tables and graphs. One way to learn effectively for children with special needs is to learnto color. The existence of these changes can be concluded that the coloring game method has apositive effect to improve the concentration of learning in children with intellectual disabilitymoderate in YPAC Makassar